2020
DOI: 10.1128/aem.02607-19
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cecal Microbiota in the Differential Resistance of Inbred Chicken Lines to Colonization by Campylobacter jejuni

Abstract: Campylobacteriosis is the leading foodborne bacterial diarrheal illness in many countries, with up to 80% of human cases attributed to the avian reservoir. The only control strategies currently available are stringent on-farm biosecurity and carcass treatments. Heritable differences in the resistance of chicken lines to Campylobacter colonization have been reported and resistance-associated quantitative trait loci are emerging, although their impact on colonization appears modest. Recent studies indicated a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…At 5 dpi, no signi cant difference in caecal colonisation by C. jejuni was observed between the two lines. These results indicate that line 6 1 is relatively resistant to C. jejuni M1 during early colonisation, as reported for other strains [20,21,29].…”
Section: Challenge Of Line 6 1 and Line N Birds With C Jejuni M1 Consupporting
confidence: 84%
See 2 more Smart Citations
“…At 5 dpi, no signi cant difference in caecal colonisation by C. jejuni was observed between the two lines. These results indicate that line 6 1 is relatively resistant to C. jejuni M1 during early colonisation, as reported for other strains [20,21,29].…”
Section: Challenge Of Line 6 1 and Line N Birds With C Jejuni M1 Consupporting
confidence: 84%
“…Previously, Boyd et al reported resistance to cloacal and caecal colonisation was apparent in line 6 1 compared to line N from 4 to 20 dpi [20], a discrepancy with this study likely due, in part, to the different C. jejuni strains used by Boyd (C. jejuni 14N and 81-176) and in this report (C. jejuni M1). Chintoan-Uta et al recently reported line N birds to be colonised by C. jejuni 11168H at c. 10 4 CFU/g caecal contents 9 dpi at 3 weeks-of-age whereas the challenge strain was absent at the limit of detection by direct plating at this time in line 6 1 birds [29]. M1 rapidly colonises the chicken caeca from doses as low as 100 CFU [33,34] and both the rate of colonisation and caecal burden have proven greater than for other C. jejuni strains tested in the same model, including 11168H (Stevens et al, unpublished data).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Line 6 1 and N chickens not only differ in resistance to Campylobacter, but to gut colonisation by Salmonella enterica serovar Typhimurium and genetic associations have been mapped using a backcross [28]. We recently demonstrated that limited differences exist between lines 6 1 and N in their caecal microbiota and reciprocal transplants of caecal microbiota did not alter their resistance to C. jejuni colonisation, suggesting a role for host factors [29]. Here, we used RNA-Seq to investigate the caecal transcriptome of line 6 1 and N chickens, both in uninfected birds to identify differences between the lines that may underlie differential resistance to pathogens and following experimental challenge with C. jejuni.…”
Section: Introductionmentioning
confidence: 98%
“…Since we analysed caecal microbiota composition after infection, we cannot exclude that the infection by Salmonella affected this microbiota composition. Does the higher susceptibility of line A study on Campylobacter resistance between lines N and 6 1 was conducted by Chintoan-Uta and colleagues [46]. Their objectives were to transfer microbiota from the resistant line to the susceptible line and to study the Campylobacter carriage.…”
Section: Impact Of the Genetic Line On The Microbiota Compositionmentioning
confidence: 99%